Pre-School Education of the Children in the Family, the Organization and the Role of Education is Directed to the Person (Eurasian Journal of Learning and Academic Teaching, 2022)
This article discusses the rolan and originality of student-centered education in the preschool and family, and the participation of family upbringing of the children in preschool